2019
DOI: 10.1590/1678-4162-10511
|View full text |Cite
|
Sign up to set email alerts
|

Análise bioeconômica de períodos de suplementação proteico-energética na estação seca para novilhas Nelore em pastagem diferida de Urochloa decumbens

Abstract: RESUMO A suplementação proteico-energética (SPE) é uma estratégia adequada à bovinocultura de corte no período seco do ano, embora sua adoção equivocada possa comprometer seu benefício/custo. O objetivo deste estudo foi avaliar o desempenho de novilhas Nelore em pastagem diferida de Urochloa decumbens sob dois períodos de SPE, e realizar análise econômica desses sistemas de produção. O experimento foi conduzido sob delineamento inteiramente ao acaso, com 147 e 55 dias de SPE (sistemas 1 e 2, respectivamente), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Our study agrees with the findings of Silva et al (2019), comparing short-term (55 days) and long-term (147 days) protein-energy supplementation of beef heifers in the dry season. The authors observed similar body weights in the end of the dry season between treatments and reported greater economic efficiency of short-term protein-energy supplementation.…”
Section: Discussionsupporting
confidence: 92%
“…Our study agrees with the findings of Silva et al (2019), comparing short-term (55 days) and long-term (147 days) protein-energy supplementation of beef heifers in the dry season. The authors observed similar body weights in the end of the dry season between treatments and reported greater economic efficiency of short-term protein-energy supplementation.…”
Section: Discussionsupporting
confidence: 92%